Examining the Impact of Subtle Cultural Differences on Rhetorical Variation in EFL Essays - schenck, andrew (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
Past research of rhetoric has relied on simple binary comparisons between groups that either do, or do not, possess a cultural trait. While countries like Korea and the UAE may share cultural values such as an acceptance of unequal power relationships (power distance) and a preference for group action (collectivism), these traits vary in degrees of intensity. To understand how these similar cultural traits may manifest differently within rhetoric, three separate corpora of persuasive essays written in English were compiled from female learners with Arabic, Korean, and English L1s. Next, frequencies of rhetorical devices from three categories (pronoun deixis, modals, and epistemic stances) were tallied and statistically compared using Friedman’s Two-Way Analysis of Variance. Results did not reveal statistically significant differences for average frequencies, yet analysis of specific rhetorical devices within each category exposed some notable disparities between corpora. Emirati (Arabic) learners, who have a strong cultural preference for power distance, tend to lessen authority of propositions and avoid a direct connection with the reader, making an argument less personal (increasing power distance). Korean learners tend to use more direct and authoritative rhetorical strategies (decreasing power distance), while simultaneously hedging with epistemic stances to maintain some degree of power distance. Hedging also appears to support Korean collectivist values that promote conflict reduction and group cohesion. Ultimately, more research of cultural influences on rhetoric is needed to develop culturally responsive pedagogy that promotes better intercultural communication.